Effect of Anacardium humile St. Hill (Anacardiaceae) Aqueous Extract on Mahanarva fimbriolata (Stal, 1854) (Hemiptera: Cercopidae) - doi: 10.4025/actasciagron.v35i4.16597 - Melissa Grindi Bragato Pistori; Antonia Railda Roel; José Raul Valério; Marlene Conceição Monteiro Oliveira; Eliane Grisoto; Rosemary Matias (Acta Scientiarum. Agronomy, 2013)
The study of plant-derived substances for the control of insect pests is desirable in the attempt to discover less toxic insecticides that are safe for the environment. Indeed, extracts from the cashew of the savannah, Anacardium humile, have shown insecticidal activities against certain insects. The sugarcane root spittlebug Mahanarva fimbriolata is considered an important pest of sugarcane, causing severe damage and significant yield reductions. The aim of this study was to evaluate the effect of the aqueous extract of A. humile (0.05, 0.4 and 1.0%) on M. fimbriolata. The application of the aqueous extract of Anacardium humile resulted in 53.1% nymphal mortality at a concentration of 1.0%, which was significantly higher than that observed in the negative control. The nymphal period and longevity of M. fimbriolata, however, were not affected by the aqueous A. humile extract.